Assessment of radiation dose hazards caused by radon and its progenies in tap water by the human dosimetric model - Jinlong Yong; Qian Liu; Baoshan Wu; Youhua Hu; Guangwen Feng (IWA Publishing, 2021)
Radon is readily soluble in water, and radon exposure caused by household water consumption may pose a threat to public health. In this study, the radon concentration in the tap water of residential buildings was measured, and the average value was 543.33 mBq L−1, which was in line with the radon concentration limit recommended by USEPA (11.11 Bq L−1) and EURATOM (100 Bq L−1), and also within the range of the results of radon concentration measurements in tap water in other countries or regions. Through water bath heating at different temperatures, the radon retention curves of multiple groups of samples at different temperatures were fitted and analyzed. The results showed that the radon retention continued to decrease between 25 and 70 °C, remained stable between 70 and 85 °C, and then continued to decline slowly. Combined with the measurement results, the effective doses of α- and β-particles emitted by 222Rn and its progenies to residents respiratory and alimentary tissues and organs were calculated using the computational model provided by ICRP under two typical water scenarios of shower and drinking water, and the results show that radon exposure caused by normal water consumption will not pose a serious threat to public health. HIGHLIGHTS The radon concentration of domestic tap water in Urumqi, Xinjiang was measured.; The variation trend of radon concentration in tap water with temperature was analyzed.; The radiation dose contributed by radon exposure to residents under different water-use scenarios was calculated based on the actual water temperature.; The radiation doses to human organs from the α and β decay progenies of radon were calculated.;